Development Of Montage-Based Learning Module For Drawing Imaginative Picture Lesson For Grade III Students - Gufroni, Ulya; Setiawan, Deni (Universitas Negeri Semarang, 2019)
This research is motivated by arts education learning problems in 60% of students who have not reached the Minimum Exhaustiveness Criteria. Based on the data of the low learning outcomes, efforts are needed to fix the learning process of arts education, especially about teaching materials. This study aims to develop, determine the feasibility of media, and the effectiveness of the use of montage-based learning module on the material to create imaginative images of arts education subjects in third grade Patemon 02 Primary School Semarang District. This research type is Research and Development withmodel development method Borg & Gall. The results of large-scale test learning have increased with the gain of N-gain of 0.69 which is included in the criterion is. Questionnaire responses students and teachers in good criteria. The conclusion of this research was a montage-based learning module feasible to be used in learning arts education material to create imaginative and effective images for use on learning SBK on student learning outcomes.